A rationale and framework for sharing mindfulness in trauma-dense communities in South Africa - Simon Whitesman (South African Family Practice)
Mindfulness has its historical roots in the teachings of the Buddha. The core of these teachings addresses the causes and relief of human suffering. It is a way of being with experience, through awareness of the present moment, in service of compassion and wisdom. Its universal applicability lies in the fact that it is an innate human capacity, which can be developed through practice. Mindfulness has moved into broader contemporary society through the emergence of mindfulness-based interventions (MBIs) over the last 50 years and an associated robust research base. Mindfulness-based pedagogy has been largely restricted to first-world countries although a 2-year training at Stellenbosch University has been an exception to this. Research based on the experience of graduates of this programme has resulted in a new, emergent curriculum that is more context- and trauma-sensitive, to better meet the challenges of the local setting, and to make learning how to share mindfulness with others more accessible, relevant and Afro-centric.